2019
DOI: 10.1007/s00167-019-05765-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural allograft impaction enables fast rehabilitation in opening-wedge high tibial osteotomy: a consecutive case series with one year follow-up

Abstract: Purpose Painful and slow recovery are the presumed disadvantages after opening-wedge high tibial osteotomy (HTO) and play a role in favouring arthroplasty as treatment for moderate isolated medial knee arthritis. The primary study objective was to investigate the efect of press-it structural impacted bone allograft with locking plate ixation on early ambulation, postoperative pain levels, and resumption of daily-life activities in opening-wedge HTO. Methods A prospective consecutive opening-wedge HTO case seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Patients receiving the vancomycin‐soaked femoral head allograft were three times more likely to participate in physiotherapy on POD1—allowing for greater ambulatory distance and reduction in PCA use. Pain reduction with the use of an impacted allograft was similarly demonstrated by Van Genechten et al [33] who demonstrated an improvement of pain scores from preoperative baseline as early as the first‐week postoperatively. Suggesting that the well‐fitted allograft confers improved stability over the osteotomy site and redistributes axial loading forces on the load‐bearing plate and screws to the reduced pain and enable early ambulation by their study cohort [33].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Patients receiving the vancomycin‐soaked femoral head allograft were three times more likely to participate in physiotherapy on POD1—allowing for greater ambulatory distance and reduction in PCA use. Pain reduction with the use of an impacted allograft was similarly demonstrated by Van Genechten et al [33] who demonstrated an improvement of pain scores from preoperative baseline as early as the first‐week postoperatively. Suggesting that the well‐fitted allograft confers improved stability over the osteotomy site and redistributes axial loading forces on the load‐bearing plate and screws to the reduced pain and enable early ambulation by their study cohort [33].…”
Section: Discussionmentioning
confidence: 64%
“…Osteotomy gap fillers such as PEEK implants, structural allografts (e.g. Femoral head allografts) and autografts have shown similar benefit in reducing postoperative pain [19, 23, 33]. Polacek et al [23] successfully achieved day‐case surgery for MOW‐HTO using intraosseous PEEK implants, making day cases for MOW‐HTO is possible, with minimal complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 , 23 Van Genechten et al showed that the graft provides additional stability to the osteotomy site, redistributes the axial load, shares the pressure on the locking screw and plate, and reduces post-operative pain. 24 Previous studies recommended bone graft filling for high-risk patients with large correction angles, severe obesity, heavy smoking history, and low bone mineral density. 16 , 17 , 25 In this study, we found that allogeneic bone graft, opening width, and history of diabetes were independent factors affecting the progress of early post-operative healing at 6 months post-surgery.…”
Section: Discussionmentioning
confidence: 99%